A multi-body model of a springboard in gymnastics - Lehmann, T.; Lorz, A.; Schleichardt, A.; Naundorf, F.; Knoll, Kl.; Eckardt, F.; Witte, K. (Science of Gymnastics Journal, 2020)
In order to develop and optimize movements in gymnastics vault, knowledge of take-off velocity and angular momentum is important. Due to the short times of contact on the springboard, high-frequency kinemetric methods are very time-consuming for the determination of the take-off parameters. A multi-body model of a springboard was developed to determine the take-off forces to calculate specific take-off parameters. The Gymnova springboard was modeled using the simulation environment software alaska. The evaluation under dynamic conditions was carried out with a falling mass test, drop-jumps and forward handspring. The evaluation was done on the parameters of the ground reaction forces (GRF): force impact (p) and maximum vertical force (Fmax). For the drop-jump and forward handspring simulation the real measured acceleration of the upper board was given as input parameter in the model. When comparing the vertical displacement of the real and the modelled upper board, a discrepancy of 6.1 % can be observed. For the falling mass test differences for p=0.4 % and Fmax=28.2 % were achieved between the real board and the model. For typical loads for the gymnastics sport, drop-jumps have been used. There were realized differences of up to 8.4 % for Fmax and 6.8 % for p. For the final stage of the review, forward handstand vaults were examined. Horizontal and vertical forces were investigated. Through thorough evaluation on several stages, it was possible to develop a springboard model that is suitable to calculate the GRF under dynamic conditions successfully in 2-d. Therefore, the forces acting on the take-off position can be calculated. Take-off parameters can be determined from these forces. This evaluation also shows that the horizontal forces in especial have to be observed.